Pengaruh Atmosphere, Fasilitas, dan Word Of Mouth Terhadap Minat Menginap Di Hotel - Wijaya, Rendy; Manurung, Tarida Marlin Surya; Srihadi, Cecilia V.; Utari, Wulandari Dwi (Jurnal Ilmiah Manajemen Kesatuan, 2019)
This study aims to analyze the effect of Atmosphere, Facilities, and Word of Mouth on the Interest of the Guests' Stay at Padjadjaran Suites Resort and Convention Hotel Bogor Nirwana Residence. To answer the purpose of the study used multiple regression tests which include simultaneous and partial tests as well as the coefficient of determination test. Determination of the number of samples carried out by the Roscoe technique of 100 guests and then determined as respondents with a purposive sampling technique. The results showed that the atmosphere partially influences the interest in staying guests in hotels, facilities partially influences the interest in staying guests in hotels, and Word of Mouth partially influences the interest in staying guests in hotels, as well as from the results of simultaneous testing or F tests obtained the results of Atmosphere, Facilities and Word of Mouth have a positive effect on Interest in Stay. Whereas in the multiple regression table the Atmosphere variable 0.282 states a score of 0.282, the Facility variable 0.365 states a score of 0.365 and in the Word of Mouth variable 0.663 states a score of 0.663 and an R square value of 0.544 is obtained, which means the dependent variable is influenced by the independent variable of 54, 4% while the remaining 45.6 is influenced by other variables not examined Keywords : atmosphere, facilities, word of mouth, attitude, stay interest